Chondrocyte hypertrophy in skeletal development, growth, and disease. Issue 1 (27th March 2014) - Sun, Margaret Man‐Ger; Beier, Frank
Abstract : Most of our bones form through the process of endochondral ossification, which is tightly regulated by the activity of the cartilage growth plate. Chondrocyte maturation through the various stages of growth plate physiology ultimately results in hypertrophy. Chondrocyte hypertrophy is an essential contributor to longitudinal bone growth, but recent data suggest that these cells also play fundamental roles in signaling to other skeletal cells, thus coordinating endochondral ossification. On the other hand, ectopic hypertrophy of articular chondrocytes has been implicated in the pathogenesis of osteoarthritis. Thus, a better understanding of the processes that control chondrocyte hypertrophy in the growth plate as well as in articular cartilage is required for improved management of both skeletal growth disorders and osteoarthritis. This review summarizes recent findings on the regulation of hypertrophic chondrocyte differentiation, the cellular mechanisms involved in hypertrophy, and the role of chondrocyte hypertrophy in skeletal physiology and pathophysiology. Birth Defects Research (Part C) 102:74–82, 2014. © 2014 Wiley Periodicals, Inc.